Effect of different dilution rate of guava juice extender on malin ram spermatozoa at 4°c and room temperature - Siti Fariza Binti Sahaman (2018)
Semen extender is vital in animal reproduction especially in artificial insemination. The ingredients used in semen extender vary throughout the world; nevertheless there is a lack of local fruits usage as an alternative ingredient in Malaysia. Tropical fruits used as alternative ingredients in semen extender are gaining more attention recently. This study was conducted to assess the effect of the guava juice extender on the sperm motility, progressive motility, path velocity (VAP) and progressive velocity (VSL) at 4°C and room temperature (RT). Guava juice extender was prepared by adding 20 ml of the supernatant with standard extender. Semen collected was diluted with control extender at 1:9, and with guava extenders of dilution 1:5, 1:10, 1:15 and 1:20. Each group of 4°C and RT (n=5), where each sample was supplemented with 0.1 ml of Malin ram semen. The samples were assessed with Computer Assisted Semen Analyser (CASA) at 0 hour, after 4-5 hours and after 16-17 hours. The sperm characteristics were analysed through ANOVA. The results showed that sperm manage to survive in the guava juice extender although, after 16-17 hours chilled, dilution 1:5 extender was significantly high in motility (75.7%), progressive motility (37.0%), VAP (75.9 μm/s), and VSL (55.0 μm/s). Dilution 1:15 was significantly high in terms of VAP (79.9 μm/s) and VSL (63.0 μm/s), after 16-17 hours storage in room temperature. Dilution 1:5 was significantly high in motility (25.7%) and progressive motility (3.7%) after 16-17 hours of storage at room temperature. In conclusion, dilution 1:5 of guava juice can be used as an alternative in semen extender for ram in chilled storage.